458 Tackling racism through simulation: challenging conversations. (17th August 2022) - Berg, Richard; Hall-Jackson, Megan; Penumala, Viswa Vani; Anpananthar, Amutha
Abstract : Aims: Equality and diversity are strongly embedded within the ethos of the National Health Service (NHS) and diversity is a ubiquitous part of mandatory training. Despite this training, many healthcare professionals across all ranks either face racism or witness racism. Often racism is not addressed openly and effectively in the clinical work areas. To discuss such a sensitive topic, we used a different approach in our hospital; an educational session to trainees using simulation scenarios. In doing so, we aimed to improve awareness, create a discussion about racism and improve awareness about how to act when racism or discriminatory comments are witnessed. Methods: After discussion with leaders and stakeholders within our NHS trust, we sensitively designed two communication scenarios using experiences from reported incidents. Firstly, a participant was asked to speak to an actor playing a parent of a child with an acute illness. The parent had just made a racial insult towards a colleague, although the actual insult was not used in the scenario. Secondly, a participant was asked to speak to an actor playing a 15-year-old admitted to a paediatric ward with an acute mental health crisis, who made a racial insult towards a colleague. The scenarios were followed by a debrief of the participants and observers, by trained facilitators. The participants were signposted to online resources and the trust guideline was discussed. We obtained participant feedback through a pre- and post- simulation questionnaire. Results: 9 doctors attended our pilot session, including paediatric trainees, GP trainees and Foundation doctors. The pre-course questionnaire highlighted the prevalence of racism in the National Health Service; 22% of attendees had suffered from racist or discriminatory behaviour in the workplace, and 55% of attendees had witnessed racist or discriminatory behaviour in the workplace directed at a colleague. However, most trainees (77%) had not attended face-to-face equality and diversity training before our simulation session as it is usually delivered online. The session was well received; it was rated 4.8/5 by participants for educational value. Most participants actively participated in the debrief and most of comments were positive, with comments such as 'finally addressing an important topic'. One doctor said it felt 'unpleasant' to perform the simulation in front of colleagues which generated much discussion amongst the faculty. A facilitator offered a personal debrief to this doctor to ensure psychological safety. Conclusion: Many of our participants had experience of suffering from, or witnessing, racism in the workplace. We showed that simulation can be used to have these challenging conversations while also increasing awareness of existing resources. However, extra care must be taken to ensure that the simulation environment is psychologically safe for all. We have taken on the feedback and in the future, we will consider inviting a psychologist for the debrief, are recording videos of semi-scripted scenarios to debrief, offer 1:1 debriefs and signpost participants to support available within the trust.